AMISAN WEDDING TRADITION IN KALIJERING PURWOREJO VILLAGE - Akhmad Muhaini; Muhajir Muhajir; Novia Nugraeni Fillaili (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2023)
Amisan marriage is a marriage performed by a couple who are still cousins. Cousin marriage which is commonly called amisan marriage in Kalijering Village is a marriage ban that has existed since ancient times, where the marriage is still running today and there is a tradition that must be carried out by the bride and groom if they continue to have a fishy wedding. This research uses qualitative research methods with the principle of understanding the object under study in depth and conducting research directly into the field (field research). In addition, this study uses inductive thinking patterns based on concrete experiences which are then used to review the practice of fishy marriage which is prohibited in Kalijering Village. As for data collection in this study, conducting interviews with fisherman marriage actors and several communities. In analyzing the author uses qualitative analysis based on Islamic law which can be concluded that fish-to-toe marriage is not prohibited and permissible, even though in Islam there is a recommendation to marry someone who is not a close relative such as a cousin. In addition, this amisan marriage is a valid 'urf and in carrying out this marriage does not look at it from the perspective of kafaah.